2023
DOI: 10.1111/jcpe.13917
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inflammatory index in relation to salivary cytokine concentrations and periodontitis: A cross‐sectional analysis

Sanna Syrjäläinen,
Satu Männistö,
Eija Könönen
et al.

Abstract: AimTo examine the associations of dietary inflammatory index (DII) with salivary cytokine concentrations and periodontitis after controlling for body mass index (BMI), socio‐demographic factors and lifestyle.Materials and MethodsSubgroups from two Finnish surveys, DILGOM 2007 and Health 2000, were included (total n = 727). The DII scores were calculated based on a food frequency questionnaire. Periodontal status was assessed with a cumulative risk score in DILGOM 2007 and by pocket depth measurement in Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…Various diets were found to be associated with periodontitis in different ways, highlighting the significant impact of nutrition on oral health. One study has found a latent correlation between diet and periodontitis, with their interconnection established through factors beyond diet-dependent inflammatory propensities (Syrjäläinen et al, 2023). For example, vegetarians, compared to non-vegetarians, have lower periodontal pocket depth (PPD) and less gingival bleeding (Staufenbiel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Various diets were found to be associated with periodontitis in different ways, highlighting the significant impact of nutrition on oral health. One study has found a latent correlation between diet and periodontitis, with their interconnection established through factors beyond diet-dependent inflammatory propensities (Syrjäläinen et al, 2023). For example, vegetarians, compared to non-vegetarians, have lower periodontal pocket depth (PPD) and less gingival bleeding (Staufenbiel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%